Incidental learning strategy to expand english language vocabulary among students of ninth year “f” of educación general básica afternoon session, at colegio de bachillerato “Beatriz Cueva de Ayora” in the city of Loja during the 2020 – 2021 school year - Mendoza Cuenca, Anthony Ronaldo (2021)
The present research aimed to expand English language vocabulary through incidental learning strategy among students of ninth-year “F” of Educación General Básica afternoon session, at Colegio de Bachillerato “Beatriz Cueva de Ayora” during the 2020-2021 school year. The methods used in this investigation were the scientific, descriptive, statistical, and the analytic-synthetic. These methods helped to collect, describe, process and interpret the obtained data. To evaluate twenty students’ vocabulary knowledge and gather information about their attitudes regarding incidental learning, instruments like tests and questionnaires, were implemented. Observation sheets and field notes served to register students’ development and perception towards incidental learning. The results reveal that students’ expanded their vocabulary knowledge in an excellent way as well as improved aspects like word spelling, denotation, parts ofthe speech, and synonymy. On the whole, this strategy encouraged students to participate actively in class generating their own knowledge, and consequently, they became independent learners.